PURIFIKASI PARSIAL DAN KARAKTERISASI ß-GALAKTOSIDASE Lactobacillus plantarum B123 INDIGENOS DAN HIDROLISIS LAKTOSA UNTUK PRODUKSI SUSU ULTRA HIGH TEMPERATURE RENDAH LAKTOSA - Tatik Khusniati; Neny Mariyani; Hanifah Nuryani Lioe; Didah Nur Faridah; Abdul Choliq; Sulistiani Sulistiani (Research Center for Chemistry - LIPI, 2015)
β-Galactosidase is enzyme which hidrolyze lactose to glucose and galactose. This enzyme is used in production low lactose milk for consumption human which have lactose intolerance. Partial purification of β-galactosidase is important to be conducted to increase β-galactosidase activity in order to its hydrolysis potency on UHT milk lactose increased.This research was aimed to production by partially purification and characterization indigenous β-galactosidase from Lactobacillus plantarum B123, and lactose hydrolysis for production low lactose UHT milk. Partially purification were precipitation following dialysis. Characterization included optimazion and stabilization of enzyme, while lactose hydrolisis for production low lactose UHT milk was detected by enzymatic GOD-POD kit. The results showed that production of β-galactosidase by using partial purification increased from 21.51 ± 0.23 U/mL (crude) to 106.34 ± 0.56 U/mL (dialysis). The optimum crude β-galactosidase activity was reached in precipitation by using 60 % ammonium sulphate. The purity of crude β-galactosidase increased 3.71 times after precipitation, and 14.28 times after dialysis. Characterization of β-galactosidase showed that optimum activities of crude and dialyzed β-galactosidase were at pH 6.5 and 50 oC, respectively. Stability of crude β-galactosidase incubated for 1 h were at pH: 5.0-8.5 and 25-50 °C. Specific activity of crude β-galactosidase was 15.05 U/mg protein, while that dialyzed β-galactosidase was 109.58 U/mg protein. Lactose hidrolysis to produce low lactose UHT milk showed that glucose concentration increased with the increase of hidrolysis time. Time needed to hidrolyze lactose 50 % with 4.8 U/mL β-galactosidase at 50°C was 6.08 h. In conclusion that indigenous β-galactosidase from Lactobacillus plantarum B123 purified partially can be used as lactose hidrolyzer in production of low lactose UHT milk.Key words : b-galactosidase, indigenous Lactobacillus plantarum B123, purification, lactose hidrolysis, UHT Milk